Key Considerations for Real-Time Object Recognition on Edge Computing Devices - Nico Surantha; Nana Sutisna (Applied Sciences, 2025)
The rapid growth of the Internet of Things (IoT) and smart devices has led to an increasing demand for real-time data processing at the edge of networks closer to the source of data generation. This review paper introduces how artificial intelligence (AI) can be integrated with edge computing to enable efficient and scalable object recognition applications. It covers the key considerations of employing deep learning on edge computing devices, such as selecting edge devices, deep learning frameworks, lightweight deep learning models, hardware optimization, and performance metrics. An example of an application is also presented in this article, which is about real-time power transmission line detection using edge computing devices. The evaluation results show the significance of implementing lightweight models and model compression techniques such as quantized Tiny YOLOv7. It also shows the hardware performance on some edge devices, such as Raspberry Pi and Jetson platforms. Through practical examples, readers will gain insights into designing and implementing AI-powered edge solutions for various object recognition use cases, including smart surveillance, autonomous vehicles, and industrial automation. The review concludes by addressing emerging trends, such as federated learning and hardware accelerators, which are set to shape the future of AI on edge computing for object recognition.